1997
DOI: 10.1021/ie9606350
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the Absorption of CO2 in Alkaline Buffers by Organic Solutes:  Relation with Degree of Dissociation and Molecular OH Density

Abstract: Absorption of CO2 in a wetted-wall column by 0.5 M Na2CO3/0.5 M NaHCO3 buffer with and without various concentrations of saccharose, fructose, glucose, formaldehyde, glycerin, methanol, or ethanol was measured under conditions in which the reaction of CO2 was of pseudo-first-order. For the purposes of comparison, experiments were also carried out with arsenite in both buffer and pure water. For all of these solutes, the absorption enhancement factor increased with solute concentration. Rate constants k c for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 23 publications
2
13
0
Order By: Relevance
“…When saccharides are components of solutions, the shortening of reaction time is most probably caused by the increase of the CO 2 absorption rate. Vasquez et al [36] reported the enhancement of CO 2 adsorption rate in alkaline buffers when fructose, glucose, or sucrose was added to the solutions. The increase in CO 2 mass transfer from the gas phase to the liquid phase was related to the number of hydroxyl groups in the solute molecules and for the solution containing sucrose was higher than for solutions with glucose of fructose.…”
Section: Resultsmentioning
confidence: 99%
“…When saccharides are components of solutions, the shortening of reaction time is most probably caused by the increase of the CO 2 absorption rate. Vasquez et al [36] reported the enhancement of CO 2 adsorption rate in alkaline buffers when fructose, glucose, or sucrose was added to the solutions. The increase in CO 2 mass transfer from the gas phase to the liquid phase was related to the number of hydroxyl groups in the solute molecules and for the solution containing sucrose was higher than for solutions with glucose of fructose.…”
Section: Resultsmentioning
confidence: 99%
“…Hence most of these catalysts have been evaluated for their activities at pH > 10. The molecules tested were acetaldehyde hydrate, acetate, arginine, arsenite, , arsenious acid, boric acid, ,, butyl chloral hydrate, chloral hydrate, chloral alcoholate, diacetyl hydrate, hypobromous acid, hypochlorous acid, , copper sulfate, ethanol, formaldehyde, ,, fructose, germanic acid, , glucose, glycerin, glycine, glyoxal hydrate, methanol, phosphate, , phosphite, proline, rhodium hydride, methylene glycol, saccharose, sarcosine, selenic acid, , silicic acid, , vanadium­(V) oxide, telluric acid, , sodium acetate, sodium bisulfate, sodium orthovanadate and zinc sulfate . Most of these inorganic chemicals have different oxidation states depending on pH .…”
Section: Catalyzed Hydration Of Co2mentioning
confidence: 99%
“…Once the gas−liquid exposure time t e and the total contact area A have been calculated as described previously, the overall pseudo-first-order rate constant k c can be obtained by fitting eq 2 to the experimental data, and the enhancement factor E and Hatta number Ha can be calculated: …”
Section: Theory and Experimental Designmentioning
confidence: 99%
“…The concentrations used, which for each individual catalyst are within the range used in the previous study, are listed in Table together with the corresponding values of relevant concentration-dependent physical properties. The experimental procedure and the reactor, a wetted-wall column, were exactly as reported previously 2 Physical Properties of a Solution of CO 2 Absorption Enhancers in 0.5 M Sodium Carbonate/0.5 M Sodium Bicarbonate Buffer, with the Corresponding Values of k c , the Overall Rate Constant for the Reaction of CO 2 , at 298.1 K [saccharose] (kmol/m 3 )[arsenite] (kmol/m 3 )[formaldehyde] (kmol/m 3 )ρ (kg/m 3 )μ ×10 3 (kg/(m·s)) C e × 10 3 (kmol/m 3 ) D × 10 9 (m 2 /s) k c (1/s) 0.073 0.005 1081.9 1.403 18.78 1.47 5.35 0.073 0.010 1081.9 1.403 18.78 1.47 6.87 0.073 0.015 1081.9 1.403 18.78 1.47 8.39 0.146 0.005 1091.8 1.533 18.21 1.37 8.31 0.146 0.0075 1091.8 1.533 18.21 1.37 9.05 0.146 0.010 1091.8 1.533 18.21 1.37 9.79 0.146 0.0125 1091.8 1.533 18.21 1.37 10.53 0.146 0.015 1091.8 1.533 18.21 1.37 11.28 0.219 0.005 1102.1 1.668 17.75 1.27 11.25 0.219 0.010 1102.1 1.668 17.75 1.27 12.71 0.219 0.015 1102.1 1.668 17.75 1.27 14.16 0.094 0.27 1093.7 1.490 18.60 1.40 10.46 0.146 0.18 1091.8 1.534 18.21 1.36 10.00 0.146 0.27 1100.9 1.575 18.21 1.33 11.51 0.146 ...…”
Section: Theory and Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation